Enhancing listening skills through technology for fll (2024)
During my internship at Colegio Santa Teresita in San Pelayo, I focused on enhancing listening skills among secondary education students. Situated in an urban area catering primarily to socio-economically disadvantaged students, the school adopts a holistic approach to English language learning, integrating diverse pedagogies and educational technologies. As overseer of four ninth-grade groups, each comprising approximately 40 students, I tailored teaching practices to meet the unique needs of each group while fostering an inclusive and participatory learning atmosphere. This report sheds light on the challenges and strategies involved in adapting teaching methods within diverse educational contexts, emphasizing the importance of flexibility and creativity in educational practices.